2020
DOI: 10.1016/j.ebiom.2020.102800
|View full text |Cite
|
Sign up to set email alerts
|

Organoid modelling identifies that DACH1 functions as a tumour promoter in colorectal cancer by modulating BMP signalling

Abstract: Background: Dachshund homologue 1 (DACH1) is highly expressed in LGR5+ intestinal stem cells and colorectal tumours. However, the roles of DACH1 in intestinal cell stemness and colorectal tumorigenesis remain largely undefined. Methods: We used immunohistochemistry, western blotting and quantitative real-time PCR to analyse DACH1 expression in colorectal cancer (CRC) samples. CRISPR/Cas9 gene editing and lentiviral vector-mediated overexpression and shRNA-mediated knockdown of DACH1 were utilized to modulate D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…As is known, DACH1 expression was aberrantly augmented in LGR5 + intestinal stem cells. It was revealed to predetermine the stem cell proliferation and maintenance in CRC through suppressing BMP signaling (26). Consistently, in our case, DACH1 protein expression was upregulated in the COAD and READ and was highly enriched in stem cell-related GO terms, indicating DACH1 might maintain the stemness of crypt base cells and promote normal epithelium-adenoma-carcinoma progression.…”
Section: Discussionsupporting
confidence: 86%
“…As is known, DACH1 expression was aberrantly augmented in LGR5 + intestinal stem cells. It was revealed to predetermine the stem cell proliferation and maintenance in CRC through suppressing BMP signaling (26). Consistently, in our case, DACH1 protein expression was upregulated in the COAD and READ and was highly enriched in stem cell-related GO terms, indicating DACH1 might maintain the stemness of crypt base cells and promote normal epithelium-adenoma-carcinoma progression.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, our study focused on EYA1, CHRM3, and DACH1 because they had a target sequence for miR-424-5p ( Figure 4 C) and showed hypermethylation in the array data, suggesting that they were downregulated by Rg3. Additionally, these three genes had previously been reported to possess oncogenic properties in several cancer types [ 26 , 27 ], except DACH1, which functioned as either a tumor promoter [ 28 ] or suppressor [ 29 ] depending on the cancer type. Consistent with the hypermethylation status, EYA1, CHRM3, and DACH1 were downregulated by 39–95% by Rg3, as determined by our qRT-PCR assays ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…2). Collectively, these analysis in colorectal tissues suggested that Hu and colleagues have brought to light oncogenic activities that were attributable to both DACH1-v1 and DACH1-v4 long variants [25]. In light of these data, the PC3 cell line preferentially expresses DACH1-v4 and PRAD patients DACH1-v1, however both isoforms have oncogenic potential.…”
Section: Dach1 Isoforms In Prostate Adenocarcinoma Patients (Prad)mentioning
confidence: 95%
“…Hu et al reported that DACH1 was expressed in intestine crypt basal cells and that DACH1 was necessary for the formation of tumor organoids, which were considered by the authors to serve as a functional assay of tumorigenesis. Moreover, high expression of DACH1 in colorectal cancer at all stages of tumor progression correlated with poor prognosis [25].…”
mentioning
confidence: 99%